Produção de hidrogênio utilizando precursores derivados de hidrotalcita e suportados em aluminato de magnésio na reforma do GLP - Ferreira, Rondinele Alberto dos Reis (2016)
The reform of hydrocarbons for hydrogen production has been widely studied, and liquefied petroleum gas (LPG) may be a promising raw material for these processes, since it is easy to store and it has a vast transportation and broad distribution network. Therefore, the objective of this work was to study the steam reforming and oxidative of LPG using catalysts derived from hydrotalcite-type structure and supported on magnesium aluminate. The catalysts derived from the hydrotalcite-type structure were synthesized by coprecipitation with molar ratio to form hydrotalcites M3+/(M2++ M3+) equals to 0.25. Nickel catalysts supported on magnesium aluminate (10, 15 and 20 wt% of Ni) were synthesized by coprecipitation technique (support) and dry impregnation (Ni). The characterization of the catalysts was performed by fluorescence analysis X-ray (XRF), BET surface area, X-ray diffraction at room temperature, temperature programmed reduction (TPR), thermogravimetric analysis (TGA) and differential thermal (DTA), in situ X-ray diffraction (in situ XRD) and X-ray absorption (XAS) spectroscopy. For hydrotalcite derived catalysts the higher the substitution of Mg2+ by Ni2+, the lowest was the temperature for the reduction of the precursor. This was probably due to the lower thermal stability of the structure. These results were observed in the analysis of TPR and in situ XRD reduction. It was also observed that it was possible to synthesize catalysts with 47.5% of Ni content with dispersion of 33.1%. Regarding the Ni catalysts supported on magnesium aluminate, it was found that coprecipitation technique allowed the formation of the support structure (MgAl2O4). After of the reduction it was observed that the supported catalysts showed lower dispersions with increasing nickel content. During the reaction period all catalysts showed the formation of the same products for steam reforming: H2, CO, CH4 and CO2. Catalysts derivatived from hydrotalcite-type structure showed conversions of LPG between 70 and 30%, and the catalyst Ni1.64Mg1.36Al presented the highest conversion (around 70%) and lower deactivation by coke deposition among all the samples studied. In the oxidative reforming process, for the catalyst Ni1.64Mg1.36Al, a decrease in the stability and a slight increase of carbon accumulation (~ 7%) was observed. In the oxidative reforming for the samples supported on magnesium aluminate both the oxidation of the catalyst bed and carbon deposition were observed, leading to deactivation of the catalysts. The study of reforming reactions at higher temperatures (1073 and 1173 K) was performed for the Ni1.64Mg1.36Al sample, which showed higher catalytic activity. The increase of temperature in the presence or absence of oxygen resulted in higher conversions of LPG, an increase in H2 formation and smaller coke deposits.